TPACK’s Roles in Predicting Technology Integration during Teaching Practicum: Structural Equation Modeling - Muhammad Sofwan; Akhmad Habibi; Mohd Faiz Mohd Yaakob (Education Sciences, 2023)
The current study aims to report the role of technological pedagogical and content knowledge (TPACK) in the integration of technology by preservice teachers during teaching practicum. As this study employed a survey as its methodological approach, instruments measuring TPACK and the integration of technology during teaching practicum were developed based on prior studies and validated through content validity and a pilot study. The main data (n. 1333) were analyzed through the partial least squares structural equation model (PLS-SEM), supported by importance performance map analysis (IPMA). The study’s results were satisfactory in determining the scale’s validity and reliability. The structural model shows that all the hypothetical interactions were positively significant. The strongest relationship between the TPACK factors emerged between technological pedagogical knowledge (TPK) and TPACK. Additionally, technology integration was most significantly affected by TPACK.